UPAYA MENINGKATKAN KEMAMPUAN MENULIS PUISI MELALUI MEDIA GAMBAR SISWA KELAS V SDN 12 BETUNG KABUPATEN BANYUASIN - Septianalisa; Dessy Wardiah; Siti Rukiyah (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2026)
This study aims to improve the poetry writing skills of fifth-grade students at SDN 12 Betung, Banyuasin Regency, through the use of picture media as a visual stimulus in Indonesian language learning. The study employed a Classroom Action Research (CAR) design following the Kemmis and McTaggart model, conducted in two cycles. Each cycle comprised four stages: planning, action, observation, and reflection. The research subjects were 23 fifth-grade students at SDN 12 Betung in the 2024/2025 academic year. Data were collected through poetry writing tests, student activity observation sheets, and learning process documentation.The results demonstrated significant improvement in poetry writing skills across cycles. The mean score increased from 63.70 in the pre-cycle (13% mastery rate) to 71.52 in Cycle I (48% mastery rate), and further rose to 83.26 in Cycle II, achieving a mastery rate of 96%. Student learning engagement also improved markedly, as evidenced by increased active participation, enthusiasm, and the ability to develop ideas and imagination through picture media.This study is limited to a single classroom in one primary school; therefore, generalization of findings should be approached with caution. Practically, the findings recommend that teachers in primary education integrate picture media as a contextual and engaging strategy for creative writing instruction. Socially, this approach has the potential to cultivate early literary appreciation among elementary school students. The original contribution of this study lies in providing empirical evidence of the effectiveness of picture media in improving poetry writing skills within the underresearched primary school context of Banyuasin Regency. Keywords: Poetry Writing; Picture Media; Classroom Action Research; Primary School.